EVALUASI SIFAT KIMIA TANAH MENURUT JARAK DARI SUNGAI DI DAERAH PASANG SURUT KECAMATAN KOTA BESI, KOTAWARINGIN TIMUR, KALIMANTAN TENGAH: Basuki,1) Zubaidah, S.,1) Husin 1) - Administrator Journal (Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTThis study aims to determine the effect of the location distance from the river bank and the depth ofsoil layer to the soil chemical properties in the tidal land area. The study was conducted in April untilJune 2016 in the tidal areas of Bajarum village, District of Kota Besi, East Kotawaringin, CentralBorneo Province. The study used survey methods and soil sampling in the field, analysis of soilsamples in the laboratory and continued with analysis and description of data. Soil sampling wasconducted at distances of 250, 500, 750, 1.000, 1.250 and 1.500 meters from the Mentaya river bankat two depth soil layers (0 - 25 cm and 25 - 50 cm). The soil chemistry properties analyzed includedpH, cation exchange capacity (CEC), base saturation, organic C, N total, total P2O5, total K2O,alumunium and hydrogen exchangeable and soil fertility status. The results of study showed that: (1)The further distance of soil from the position of Mentaya river bank there is an increase of organic C,total P2O5, total N, total K2O, pH, CEC, base saturation and soil fertility status, on the contraryshowed a decrease in alumunium and hydrogen exchangeable. The limiting factor of soil fertility ismainly the low base saturation, besides that at some point observation also due to low CEC, totalP2O5 and total K2O. (2) Sub soil layer (25 - 50) cm has a higher pH and base saturation valuescompared to topsoil layer (0 - 25) cm. In contrast, topsoil layer has CEC, alumunium and hydrogenexchangeable, total P2O5, total K2O, total N and organic C values higher than sub soil layer.Keywords: distance from river, tidal soil, soil chemical properties.